1985
DOI: 10.1056/nejm198502073120601
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Fluid Secretion and Protein Hyperconcentration in Cystic Fibrosis

Abstract: To study pancreatic protein and water secretion in 28 patients with cystic fibrosis and 21 controls matched for pancreatic acinar function as defined by trypsin secretion, we used a quantitative-marker perfusion technique and continuous intravenous secretin-pancreozymin stimulation. Regardless of the level of pancreatic acinar function, secretions from the patients contained significantly higher concentrations of protein than those from the controls. Total protein output and albumin:protein ratios were not inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
117
0
7

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(135 citation statements)
references
References 32 publications
11
117
0
7
Order By: Relevance
“…This observation is based on direct evidence of reduced fluid output and increased concentration of secreted proteins in comparison with matched non-CF subjects (18)(19)(20)(21)(22). The finding of a greater reduction of fluid output in tandem with reduced enzymatic output in pancreatic-sufficient patients who develop pancreatic failure provides strong evidence for progressive pathology presumably due to ductal obstruction and acinar atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is based on direct evidence of reduced fluid output and increased concentration of secreted proteins in comparison with matched non-CF subjects (18)(19)(20)(21)(22). The finding of a greater reduction of fluid output in tandem with reduced enzymatic output in pancreatic-sufficient patients who develop pancreatic failure provides strong evidence for progressive pathology presumably due to ductal obstruction and acinar atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CF patients were refractory to secretin, a cAMPmediated secretory agonist in the pancreas. These studies were confirmed by Gaskin et al (1982) and Kopelman et al (1985Kopelman et al ( , 1988. Extensive transport studies of the exocrine pancreas have shown that HCO 3 2 is the primary anion secreted by the ductal cells, the predominate site of CFTR expression (Marino et al 1991).…”
mentioning
confidence: 71%
“…The net result of ductal function is an increased volume of alkaline fluid, allowing the highly concentrated proteins secreted by the acinar cells to remain in a soluble state. Absent or reduced CFTR channel function impairs chloride and bicarbonate transport of the ducts, which results in reduced volume and hyperconcentration of macromolecules (Kopelman et al 1985(Kopelman et al , 1988. The consequences of mutations in the CFTR gene have been shown by pancreatic function studies that indicate that CF patients have a low flow of secretions with a high protein concentration, which presumably will precipitate in the duct lumina causing obstruction and damage (Fig.…”
Section: Exocrine Pancreatic Abnormalities Exocrine Pancreatic Functionmentioning
confidence: 99%